A prospective, observational study of cerebrovascular autoregulation and its association with delirium following cardiac surgery. (18th October 2018) - Chan, B.; Aneman, A.
Summary: This aim of this prospective observational cohort study was to evaluate any association between postoperatively impaired cerebrovascular autoregulation and the onset of delirium following cardiac surgery. Previous studies have shown that impaired intra‐operative cerebrovascular autoregulation during cardiopulmonary bypass is associated with delirium. However, postoperative changes in cerebrovascular autoregulation and its association with delirium have not been investigated. One‐hundred and eight consecutive adult cardiac surgical patients without baseline cognitive dysfunction or aphasia were included in the study. Cerebrovascular autoregulation was assessed by the Pearson correlation between near‐infrared spectroscopy‐derived cerebral tissue oxygen saturation and mean arterial pressure to derive the tissue oximetry index. Cerebrovascular autoregulation was monitored for a minimum of 90 min on postoperative day 0 and postoperative day 1. Delirium was assessed throughout intensive care unit admission using the confusion assessment method for the intensive care unit. We observed delirium in 24 of the 108 patients studied. The mean (SD) tissue oximetry index was higher in delirious patients on postoperative day 0 compared with non‐delirious patients; 0.270 (0.199) vs. 0.180 (0.142), p = 0.044, but not on postoperative day 1; 0.130 (0.160) vs. 0.150 (0.130), p = 0.543. All patients showed improvement in tissue oximetry index on postoperative day 1 compared with postoperative day 0. Logistic regression analysis demonstrated tissue oximetry index on postoperative day 0 to be independently associated with delirium; odds ratio 1.05 (95%CI 1.01–1.10), p = 0.043. In conclusion, we found an association between impaired cerebrovascular autoregulation, measured by near‐infrared spectroscopy, and delirium in the early postoperative period. 개요: 이 전향적 코호트 연구의 목적은 심장수술 후 뇌혈관 자동 조절능의 장애와 섬망 발생 간의 연관성을 알아보고자 하는 것이다. 기존 연구에서 심폐우회술 중 혈관 자동조절능 장애 가 섬망과 관련이 있는 것으로 나타났지만, 수술 후 뇌혈관 자 동조절능의 변화 및 섬망과의 연관성에 대해서는 아직 연구된 바 없다. 기저에 인지기능 장애나 실어증이 없는 108명의 심장 수술 환자를 대상으로 하였다. 뇌혈관 자동조절능은 근적외 선분광분석법으로 측정한 뇌조직산소포화도와 평균동맥압 간의 피어슨 상관분석을 통하여 도출한 조직산소지수를 이용 하여 평가하였다. 뇌혈관 자동조절능 감시 기간은 수술 당일 부터 수술 후 1일까지 최소 90분 이상이었다. 섬망은 중환자실 재원 동안 confusion assessment method for the intensive care unit (CAM‐ICU)을 사용하여 평가하였다. 108명 중 24명에서 섬망이 발생하였다. 섬망이 있었던 환자들의 수술 당일 평균(표준편차) 조직산소지수는 섬망이 없었던 환자들보 다 높았다; 0.270 (0.199) vs. 0.180 (0.142), p = 0.044, 그러나 수술 후 1일에는 차이가 없었다; 0.130 (0.160) vs. 0.150 (0.130), p = 0.543. 모든 환자에서 수술 당일보다 수술 후 1일에 조직 산소지수가 증가하였다. 로지스틱 회귀분석 결과 수술 당일의 조직산소지수는 섬망의 독립적 예측인자로 나타났다; odds ratio 1.05 (95%CI 1.01‐1.10), p = 0.043. 결론적으로 근적외선 분광분석법으로 측정한 뇌혈관 자동조절능 장애는 수술 후 초기 섬망의 발생과 연관이 있었다.